Isolation, characterization and bioactivity of endophytic fungi from Withania somnifera - and NUTAN KAUSHIK, SUSHEEL KUMAR (Indian Phytopathology, 2013)
Microorganisms have been the great reservoir of the enzymes and secondary metabolites beneficial for pharmacological, agrochemical and food processing industry and thereby benefiting human being. Vast majority of microbes utilized for better plant health are soil dwelling saprophytic fungi and bacteria. Endophytes live inside the plant without causing any negative effect on plant fitness and survival and they have co-evolved with plants to help each other in their better survival (8). They live inside the plant system and complete their part or whole life cycle inside the plants, without causing any apparent disease symptom (5). Some endophytes improve the ecological fitness and provide enhanced tolerance to environmental stresses. Most of the endophytic fungi having beneficial activity or useful metabolites have been reported from specialized niche which created stress to host plant. Almost all vascular plant examined till date harbors endophytic fungi in some parts of their life cycle (8).